2010
DOI: 10.1002/jbm.a.32885
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage regeneration by bone marrow cells‐seeded scaffolds

Abstract: Different approaches exist for the treatment of small articular cartilage defects. Several studies show comparable results for autologous chondrocyte implantation (ACI) and microfracture. Unfortunately, the fibrocartilage resulting from microfracture has neither the structure nor the mechanical properties of hyaline cartilage, even though the adult mesenchymal stem cells, which immigrate into the defect, are supposed to differentiate into chondrocytes. This study was performed to examine the capacity of a reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…4 Previous evidence proved that bone marrow clots (MC) on the surface of the microfracture lesions provide an optimal environment for cartilaginous tissue repair. 5,6 However, this technique results in a repaired tissue with lower mechanical strength. This tissue is easily worn by daily activities, causing symptoms to recur and necessitating a second repair.…”
mentioning
confidence: 99%
“…4 Previous evidence proved that bone marrow clots (MC) on the surface of the microfracture lesions provide an optimal environment for cartilaginous tissue repair. 5,6 However, this technique results in a repaired tissue with lower mechanical strength. This tissue is easily worn by daily activities, causing symptoms to recur and necessitating a second repair.…”
mentioning
confidence: 99%
“…Most studies have focused on the biological factors, whereas only a few have evaluated the material and mechanical factors. Furthermore, there have been few studies on the combined stimulation of the aforesaid factors . To the best of our knowledge, this study is the first report demonstrating that LIUS, a mechanical stimulation, cooperates with a potent biomaterial scaffold (i.e., the fibrin‐HA hydrogel used in this study) on the chondrogenesis of MSCs, whereas TGF‐β3, a well‐known chondrogenic inducer, does not.…”
Section: Discussionmentioning
confidence: 79%
“…The chondrogenic differentiation of MSCs is also influenced by scaffold biomaterials that provide the 3‐D culture environment . The scaffold biomaterials are thought to provide not only a physical platform in which the cells reside, but also a functional microenvironment that can affect the physiology and activity of the cells .…”
mentioning
confidence: 99%
“…Eyrich et al demonstrated the capacity to form cartilage with chondrocyte-seeded stable fibrin gels (Eyrich et al, 2007). Wegener et al used polyester scaffolds filled with a fibrin gel (with or without chondrocytes) to repair cartilage defects in the femoral condyle in sheep (Wegener et al, 2010). This study confirmed cartilage formation and improved O'Driscoll scores in defects filled with these scaffolds.…”
Section: Fibrinmentioning
confidence: 77%